Inadequação do consumo alimentar de crianças e adolescentes com artrite idiopática juvenil e lúpus eritematoso sistêmico Inadequate dietary intake of children and adolescents with juvenile idiopathic arthritis and systemic lupus erythematosus - Michelle C. Caetano; Thaís T. Ortiz; Maria Teresa S. L. R. A. Terreri; Roseli O. S. Sarni; Simone G. L. Silva; Fabíola I. S. Souza; Maria Odete E. Hilário (Elsevier, 2009)
OBJETIVOS: Avaliar o consumo alimentar de crianças e adolescentes com artrite idiopática juvenil (AIJ) e lúpus eritematoso sistêmico (LES) por recordatório de 24 horas e relacioná-lo com características clínicas e antropométricas e com os medicamentos empregados. MÉTODOS: Em estudo transversal, avaliamos os recordatórios de 24 horas de pacientes ambulatoriais. O estado nutricional foi classificado pelo CDC, 2000. Para o cálculo da ingestão, utilizamos o software NutWin UNIFESP-EPM. Para a análise quantitativa e qualitativa, adotamos as Recommended Dietary Allowances e a pirâmide alimentar brasileira. RESULTADOS: A mediana de idade foi 12 na AIJ e 16,5 anos no LES. Na AIJ, 37,5% dos pacientes estavam em atividade de doença, e, no LES, 68,2% tinham Systemic Lupus Erythematosus Disease Activity Index > 4. Foi encontrada desnutrição em 8,3 e 4,5% dos pacientes com AIJ e com LES, respectivamente, e obesidade, em 16,7 e 18,2%. Na AIJ, o consumo excessivo de energia, proteína e lipídios foi de 12,5, 75 e 31,3%, respectivamente. No LES, o consumo excessivo de energia, proteína e lipídios foi de 13,6, 86,4 e 36,4%, respectivamente. Consumo deficiente de ferro, zinco e vitamina A foi observado em 29,2 e 50, 87,5 e 86,4 e 87,5 e 95,2% dos pacientes com AIJ e LES, respectivamente. Não houve relação significante entre consumo, atividade da doença e estado nutricional. CONCLUSÃO: Pacientes com doenças reumáticas apresentam inadequação do consumo alimentar. Ressaltamos a ingestão excessiva de lipídios e proteínas e a ingestão insuficiente de micronutrientes. OBJECTIVES: To evaluate the dietary intake of children and adolescents with juvenile idiopathic arthritis (JIA) and juvenile systemic lupus erythematosus (JSLE) using a 24-hour diet recall and relating it to the patients clinical and anthropometric characteristics and to the drugs used in their treatment. METHODS: By means of a cross-sectional study, we assessed the 24-hour diet recalls of outpatients. Their nutritional status was classified according to the CDC (2000). The computer program NutWin UNIFESP-EPM was used for food intake calculation. The Recommended Dietary Allowances and the Brazilian food pyramid were used for quantitative and qualitative analysis. RESULTS: Median age was 12 years for JIA patients and 16.5 years for JSLE patients. Among the JIA patients, 37.5% had active disease, and among the JSLE patients, 68.2% showed Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) > 4. Malnutrition was found in 8.3 and 4.5% of the JIA and JSLE patients, respectively, and obesity was present in 16.7 and 18.2%. For JIA patients, the excessive intake of energy, protein, and lipids was 12.5, 75, and 31.3%, respectively. For JSLE patients, the excessive intake of energy, protein, and lipids was 13.6, 86.4, and 36.4%, respectively. Low intake of iron, zinc, and vitamin A was found in 29.2 and 50, 87.5 and 86.4, and 87.5 and 95.2% of the JIA and JSLE patients, respectively. There was not a significant association between intake, disease activity, and nutritional status. CONCLUSION: Patients with rheumatic diseases have inadequate dietary intake. There is excessive intake of lipids and proteins and low intake of micronutrients.